Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/j.crma.2004.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Finite speed of propagation in porous media by mass transportation methods

Abstract: In this note we make use of mass transportation techniques to give a simple proof of the finite speed of propagation of the solution to the one-dimensional porous medium equation. The result follows by showing that the difference of support of any two solutions corresponding to different compactly supported initial data is a bounded in time function of a suitable Monge-Kantorovich related metric. To cite this article:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 7 publications
(11 reference statements)
1
52
0
Order By: Relevance
“…The examples considered in [22,28] showed that the pseudo-inverse form is a very powerful tool to investigate contraction properties of a semigroup in one-dimensional Wasserstein spaces. In the special case of a gradient flow (1) on P 2 , in which v = ∂F[ρ], one can formally see that the pseudo-inverse form of (1) becomes…”
Section: Contraction Properties In Wasserstein Spacesmentioning
confidence: 99%
See 4 more Smart Citations
“…The examples considered in [22,28] showed that the pseudo-inverse form is a very powerful tool to investigate contraction properties of a semigroup in one-dimensional Wasserstein spaces. In the special case of a gradient flow (1) on P 2 , in which v = ∂F[ρ], one can formally see that the pseudo-inverse form of (1) becomes…”
Section: Contraction Properties In Wasserstein Spacesmentioning
confidence: 99%
“…Let us consider the pseudo-inverse equation for (22). Let µ be a gradient flow solution to (22) and let…”
Section: Identification With L 2 Gradient Flowsmentioning
confidence: 99%
See 3 more Smart Citations